A temporal link between the Emeishan large Igneous Province (SW China) and the end-Guadalupian mass extinction - Zhou, M.; Malpas, J.; Song, X.; Robinson, Todd; Sun, M.; Kennedy, Allen; Lescher, C.; Keays, R. (Elsevier Science BV, 2002)
Previous studies have suggested that there were two mass extinction events in the Late Permian: one that occurred at the Permo-Triassic (P/T) boundary (251 Ma) and a second, smaller mass extinction that occurred 5 8 Myr earlier at the end of the Guadalupian. Many workers have argued that there is a causal relationship between large-scale volcanic activity and mass extinctions. The major mass extinction event at the P/T boundary coincides with the outpouring of huge quantities of lava that formed the Siberian flood basalt province in Russia. Courtillot et al. [Earth Planet. Sci. Lett. 166 (1999) 177 195] and Wignall [Earth Sci. Rev. 53 (2001) 1 33] suggested that the earlier Late Permian mass extinction coincided with the eruption of the lavas that formed the Emeishan flood basalt (EFB) province in SW China. However, the age of eruption of the EFB lavas is poorly constrained. Using the Sensitive High-Resolution Ion Microprobe to analyze zircons, we have established the age of the Xinjie intrusion, believed to be a feeder to the main phase of EFB volcanism, to be 2593 Ma. Hence, the formation of the EFB is coincident with a proposed extinction event at 256 259 Ma. This result supports a temporal link between the Emeishan large igneous province and the end-Guadalupian mass extinction.